Instructional Process of the Derivative Applied in Business Engineering Students in Chile - Galindo Illanes, Maritza Katherine (2024)
[Objective] The objective of this article is to present the results of the implementation of an instructional design for the teaching of the derivative for undergraduate students of Business Engineering in Chile. [Methodology] The participants in the study were ninety students of Applied Business Calculus at a Chilean university. The methodological design, based on the tools of the Ontosemiotic Approach to Mathematical Cognition and Instruction, consider various epistemic configurations in situations-problems concerning tangents, the calculation of derivatives from the rules for derivation, applications of the derivative for the calculation of maxima and minima, and analysis of graphs of functions. In addition, it integrates ICT into various activities. [Results] The results indicate that the instructional proposal for teaching the derivative overcomes some of students’ learning difficulties, as shown in various research studies. In particular, these include the difficulties that Business Engineering students have with the Euclidean conception of the tangent line, the interpretation of the derivative function and its geometric representation, the optimization of economic functions, and the application of the derivative to marginal functions. [Conclusions] It is concluded that the teaching and learning process is effective, in the sense that student learning for a specific engineering career is achieved by instruction that incorporates different interconnected epistemic configurations of the derivative, its different fields of problems, and contextual applications in their profession, together with the use of ICT resources.